Answer:
The correct option is C....
Step-by-step explanation:
First of all multiply the terms:
(x-6)(x+8)=0
x^2+8x-6x-48=0
Now solve the like terms:
x^2+2x-48=0
Now we will solve this quadratic equation by factoring:
The first terms has coefficient 1. So 1 will be multiplied by the constant term 48.
1*48= 48
Now we have to find out the two values whose product is 48 and whose sum or difference is 2(middle term).
8*6 = 48
8-6 = 2
Now break the middle term:
x^2+8x-6x-48 = 0
Now take the common from the first two and last two terms:
x(x+8)-6(x+8) = 0
(x+8)(x-6)=0
x+8=0 , x-6=0
x= 0-8 , x=0+6
x = -8 , x=6
Thus the solutions we get are: x=6 or x= -8
The correct option is C....